Exploring the diversity and phenotypic properties of culturable haloalkaliphilic bacteria from soda pans in Buhera, Zimbabwe - Ngonidzashe Mangoma; Nerve Zhou; Thembekile Ncube (Academia Biology)
Soda pans are natural aquatic environments characterised by elevated salinity, alkalinity, and carbonate and sodium content, and a unique chemical composition, creating extreme conditions for microbial occupancy. Notwithstanding their extreme physicochemical profile, soda pans harbour robust, unique and diverse bacteria that hold biotechnological potential as cheap sources of novel enzymes and metabolites that function under harsh industrial conditions. Despite the challenges involved, extremophilic bacteria have been successfully isolated from soda pans. Here, we report on haloalkaliphilic bacteria isolated from the water and sediment of a previously unexplored soda pan located in Buhera district, Zimbabwe. The isolates were characterised for their morphological, physiological and molecular traits. Isolate taxonomic and phylogenetic profiling was performed based on 16S rRNA gene sequence homology. The pH and salinity ranges allowing isolate growth, as well as their optima, were determined. Additionally, isolates were screened for their ability to produce extracellular amylases, proteases and lipases. Twenty-two isolates were obtained, nineteen of which belong to six genera under the phyla Pseudomonadota (84%) and Bacillota (16%). Isolates under the genus Vibrio were the most abundant, at 55% of identified isolates, followed by Halomonas (14%). Genera Alkalibacterium, Alkalihalobacillus, Exiguobacterium and Marinospirillum were represented by one isolate each. All isolates grew above pH 8 and 3% salinity, making them both halophilic and alkaliphilic. Lastly, all isolates were capable of producing at least one extracellular enzyme. This study clearly demonstrates the presence of culturable haloalkaliphilic bacteria in Buhera soda pans, with evidence of their ability to produce industrially important enzymes.